Non-linear histological alteration in the duodenum, Hepar, and renal mice following oral Aluminium exposure at varying doses - Faizah, Zakiyatul; Yuliawati, Tri Hartini; Rimbun; Susanto, Joni; Hendarto, Hendy (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to investigate the effects of Al exposure on the duodenum, liver, renal function, and survival rate. Aluminium (Al) is one of the heavy metals that is widely used in daily life and has a negative impact on health. A total of 51 male Balb/c mice, aged 3 months, were randomly assigned to four groups. The negative control group was administered sterile aquadest, while the treatment groups received oral administration of AlCl3 at doses of 100 mg/kg body weight (BW), 150 mg/kg BW, and 200 mg/kg BW, respectively, for 53 consecutive days via oral gavage. The ANOVA and Kruskal-Wallis tests were used in statistical analyses. The duodenal inflammation score, the severity of focal inflammation and nuclear degeneration in the liver, and the glomerular-to-renal corpuscle ratio tended to increase in the 100 mg/kg BW group compared to the control and other treatment groups. Interestingly, the highest mortality rate was not observed in the 100 mg/kg BW group. Aluminium exposure affected the histological features of the duodenum, liver, and renal function, with the most pronounced changes observed in the 100 mg/kg BW group. These findings suggest that the toxic effects of aluminium may not exhibit a linear relationship with increasing doses. Aluminium contamination is a concern even at low doses.